Women’s Work and Land Reform in Zimbabwe: A Feminist Political Economy of Social Reproduction - Tekwa, Newman (METSZETEK Társadalomtudományi Folyóirat, 2024)
While the future of work in Africa is increasingly becoming an important area of research, a feminist political economy of social reproduction holds potential to illuminate the gendered and geographical nature of women’s work in a context of radical land reform. Time-use surveys data was gathered across three study areas, two land reform and one non-land reform sites. This was complemented with in-depth and focus group discussions in the land reform sites with participants drawn from participating female and male-headed households. While literature on women’s work is accumulating, this has not been extended to integrate a feminist social reproductive lens on African rural women’s work in a context of land reform. The none or malrecognition of social reproduction by the State makes the latter an agent of depletion – a gendered form of structural and everyday violence on women. While liberating, radical land reforms, of their own, do not necessarily improve the care burden of women. This is compounded by the debt crisis crippling many countries of the global South.